Types of Injury Experienced by Rugby Athletes in Indonesia - Nur Luthfiatus Solikah; Tommy Apriantono; N Nurhasan (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Rugby is a popular sport categorized as a physical game with a high level of physical contact and significant injury risk. The purpose of this study was to find out and describe the type of injury suffered by Rugby athletes in Indonesia. This quantitative descriptive research was conducted by evaluating male rugby athletes (N = 62) experiencing injury using a questionnaire. The questionnaire questions focused on anthropometry, age when experiencing the injury, causes of injury, anatomical injury, and types of injury. The anthropometry analysis result of the Rugby athletes aged 16-30 years showed that they had an ideal body mass index (16-20 years = 21.0 ± 2.8 vs 21-25 years = 23.2 ± 1.3 vs 26-30 years = 25.9 ± 1.0). The common injuries found in Rugby athletes was acute injuries (56%) compared to overuse injuries (44%). The result also showed that 65% of 62 players suffered a lower limb injury, only 35% of the 62 players suffered an upper limb injury. In general, 53% of 62 players suffered ligament injury, where 31% of injury occurred in the Knee. The cause of injury suffered by Rugby players was physical contact with opponents. The data described that 50% of 62 players suffered injuries due to physical contact. This study indicates that physical contact is a common cause of injury to Rugby athletes, while the type of injury that often occurs is a ligament injury where the lower limb becomes the most common injury. As they get older, the risk of injury in Rugby athletes in Indonesia is increasing.